Teacher education curriculum - Flores, Maria Assunção (2016)
This chapter focuses on the key components of the curriculum of Initial Teacher education (ITE) and the ways in which it has been changing over the last years internationally. In particular, it analyses the place and role of the educational studies, subject matter studies, pedagogical studies (sometimes following a more didactic perspective) and practicum in initial teacher education programmes. The aim of the chapter is twofold: (1) to identify and contrast the ways in which the different key components are articulated in the curriculum of ITE programmes; (2) to analyse the rationale and underpinning assumptions of given models of teacher education, particularly the views and focus of the curriculum itself and the government intervention in the design of ITE programmes. It is argued that, in many contexts, teacher education curriculum has been subject of a rather restricted view in line with policies that point to a narrow perspective of school curriculum. However, it is also possible to identify programmes that integrate the key components of ITE curriculum, in particular theory and practice, subject knowledge and educational studies as well as practicum, in a more explicit way, through a research based design.